2015
DOI: 10.1016/j.jmr.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

15N CSA tensors and 15N–1H dipolar couplings of protein hydrophobic core residues investigated by static solid-state NMR

Abstract: In this work, we assess the usefulness of static 15N NMR techniques for the determination of the 15N chemical shift anisotropy (CSA) tensor parameters and 15N-1H dipolar splittings in powder protein samples. By using five single labeled samples of the villin headpiece subdomain protein in a hydrated lyophilized powder state, we determine the backbone 15N CSA tensors at two temperatures, 22 and –35°C, in order to get a snapshot of the variability across the residues and as a function of temperature. All sites p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In this case both magic-angle cross-polarization measurements and static measurements of the CSA tensors have been employed. (18, 19) The data confirmed that the structures are similar in solution and in hydrated powder states.…”
Section: Note On the Preparation Of Samples Suitable For Static 2hsupporting
confidence: 69%
“…In this case both magic-angle cross-polarization measurements and static measurements of the CSA tensors have been employed. (18, 19) The data confirmed that the structures are similar in solution and in hydrated powder states.…”
Section: Note On the Preparation Of Samples Suitable For Static 2hsupporting
confidence: 69%
“…The main sample conditions are hydrated powders with a water content of 40%, which is a typical amount of water for protein powder samples. 47−50 We confirmed the refolding procedure by measuring the 15 N backbone chemical shifts of the three core phenylalanines and additional leucine residues 45,51 (Supporting Information SI1). An additional dry sample labeled at the F58 residue corresponds to lyophilized powder without the reintroduction of water.…”
Section: ■ Materials and Methodsmentioning
confidence: 67%
“…The labeling pattern (Figure ) resulting from fluorenylmethyloxycarbonyl (FMOC)-phenylalanine-ring-d 5 in the solid-state peptide synthesis corresponds to the deuterons incorporated in all five positions of the aromatic ring. The main sample conditions are hydrated powders with a water content of 40%, which is a typical amount of water for protein powder samples. We confirmed the refolding procedure by measuring the 15 N backbone chemical shifts of the three core phenylalanines and additional leucine residues , (Supporting Information SI1). An additional dry sample labeled at the F58 residue corresponds to lyophilized powder without the reintroduction of water.…”
Section: Methodsmentioning
confidence: 71%
“…Similar to dipolar coupling, CSA provides another powerful tool for probing the motional behaviors in biosystems, for example, the dynamics of the backbone ,,,, and side chains ,, of peptides/proteins, as well as the diffusion of biomolecules such as proteins and phospholipids . In general, the size of the CSA for spin-1/2 nuclei covers a very wide range, from <5 ppm for aliphatic protons to >200 ppm for 19 F, 31 P, and 13 C, in accordance with a broad range of motional time scales.…”
Section: Csa Recoupling Techniques and Applicationsmentioning
confidence: 99%